The construction of career aspirations amongst healthcare support workers: beyond the rational and the mundane?. Issue 2 (18th February 2019) - Kessler, Ian; Bach, Stephen; Nath, Vandana
Abstract: This article engages with a literature that views the limited career aspirations of low‐paid, low‐status workers as a reasonable response to material and structural constraints. Based on four hospital trust cases studies, the article contests this view, revealing how healthcare support workers in NHS England have retained the cognitive capacity to override such constraints to develop a strong and authentic career goal to become a nurse. This goal is acknowledged by the healthcare support workers themselves as unlikely to be achieved and is therefore presented as a flight from rationality. Its emergence is explained by workplace interactions that allow such an ambition to become taken‐for‐granted. The article deepens understanding of career ambitions amongst low‐paid, low‐status workers, while adding weight to a literature suggesting that career aspirations can be driven by values and norms, not only by a means‐end rationality.